OS OBJETIVOS DO DESENVOLVIMENTO SUSTENTÁVEL – UM ESTUDO DE CASO NA EMPRESA FM PNEUS LTDA. À LUZ DA TEORIA DOS STAKEHOLDERS - PENTEADO, JEISIANE ANDRESA (2022)
Objective: to analyze the practices of the company FM Pneus Ltda. in relation to the Sustainable Development Goals and their goals, in the light of stakeholder theory. As a research problem: what are the practices of the company FM Pneus related to the Sustainable Development Goals (SDGs) Agenda 2030 and its goals, in the light of the stakeholder theory? Theoretical framework: for a better understanding of the research theme, the objective themes of sustainable development, sustainable organizations and global pact and stakeholder theory will be based. Methodology: the present work is done through a case study, with a mixed methodology, where the qualitative method was used, being carried out semi-structured interviews, field diary and direct and quantitative observation with the application of questionnaires. Results and conclusions: the results show that the company studied meets most of the SDG's, and in the view of the managers there are practices in 9 of the 17 SDG's and in the view of the employees it meets 15 of the 17 SDG's. Originality/value: helps the company to adopt new practices in relation to the SDGs, in addition to bringing the participation of its employees, who are the people who will put the SDGs into practice within the company. The research still leaves opportunities for future studies in other companies and institutions.